Legal Protection for Doctors Under Law Number 17 of 2023 Concerning Health - Tamon, Oktavian; Setiawan, Eko Wahyuddin; Sapsudin, Asep (LifeSciFi, 2025)
The security and safety of doctors is a serious concern in the health sector, especially after the occurrence of various violence against health workers. This issue has become increasingly important with the new Health Law, which is expected to provide stronger legal protection for doctors in carrying out their professional duties. This study aims to examine how legal protection for doctors is regulated in the new regulation and identify whether the protection is sufficient to ensure a sense of security at work. This research uses a normative juridical method with a statutory approach and a case approach. Data collection techniques were carried out through literature study of legal documents, laws and regulations, and relevant court decisions. Data analysis was conducted qualitatively with a descriptive-analytical approach. The findings indicate that the new Health Law contains several important provisions regarding legal protection for doctors, but there are still some legal gaps and weaknesses in implementation in the field. Therefore, it is recommended that the government strengthen legal protection mechanisms and clarify law enforcement procedures in cases of violence against doctors in order to create a safe and conducive work environment.